Dehydration of apple slices by sequential drying pretreatments and airborne ultrasound-assisted air drying: Study on mass transfer, profiles of phenolics and organic acids and PPO activity. (January 2022) - Zhu, Rui; Jiang, Sirui; Li, Dandan; Law, Chung Lim; Han, Yongbin; Tao, Yang; Kiani, Hossein; Liu, Dongfeng
Abstract: Pretreatments of either water blanching or NaCl immersion and airborne ultrasound-assisted air drying were combined to dehydrate apple slices. The drying time was found to be reduced by 1.6–69.0% compared with air drying without any pretreatment and sonication. Meanwhile, it was found that sequential water blanching coupled with air drying with sonication gave the shortest drying time. A modified diffusional model incorporating temperature-dependent moisture diffusivity ( D eff ) could simulate the apple drying process well. Water blanching pretreatment and airborne sonication were found to lower the activation energy required for the enhancement of moisture diffusive ability, and intensify water exchange on apple surface to speed up the drying process. Both water blanching and NaCl immersion significantly increased the amounts of procyanidin B2 in dehydrated apple slices. However, airborne sonication promoted the loss of procyanidin B2 in apple slices with pretreatments during air drying. In addition, sonication had no obvious influences on apple PPO activity and individual organic acids throughout drying. Overall, the sequential NaCl immersion pretreatment (or water blanching pretreatment) and drying with airborne sonication are effective to improve the quality of dried apple slices. Graphical abstract: Unlabelled Image Highlights: Pretreatments and air drying with sonication reduced apple drying time by 1.5–68.9%. A modified diffusional model with temperature factor predicted apple drying well. Water blanching and NaCl immersion enhanced procyanidin B2 content of dehydrated apple. Sonication promoted the loss of procyanidin B2 in apple samples with pretreatments. Organic acid profile and PPO activity were less affected by ultrasound-assisted drying.